Effects of Demographic Factors, Compensation, Job Satisfaction on Organizational Commitment (A Study on the Inspectorate Office of Merauke and Boven Digoel Regency) - Isnarti Trisnawati; Anita Erari; Siti Aisyah (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aimed to determine the effect of demographic factors and compensation on organizational commitment mediated by job satisfaction. This was a quantitative study using a causal analysis. The research instrument was a questionnaire with a five-point Likert scale. The research samples consisted of 109 employees of the Inspectorate Office of Merauke and Boven Digoel Regency. The data were analyzed using the SEM-PLS method. The results showed that demographic factors had a negative effect on organizational commitment and compensation, but did not have a significant effect on job satisfaction. On the other hand, compensation had a positive and significant effect on job satisfaction and organizational commitment. Similarly, job satisfaction also had a positive and significant effect on organizational commitment. Compensation can mediate the relationship between demographic factors with organizational commitment and job satisfaction. Job satisfaction can mediate the relationship between compensation with organizational commitment, but cannot mediate the relationship between demographic factors with organizational commitment.